FORMULATION AND ANTIBACTERIAL ACTIVITY OF LIQUID SOAP FROM KECOMBRANG STEM EXTRACT (Etlingera elatior) AGAINST Staphylococcus aureus - Adini Syilvi; Miftah Miftah; Yusransyah Yusransyah; Stiani Sofi Nurmay (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2026)
Kecombrang (Etlingera elatior) is a plant used by the Baduy ethnic group as a substitute for soap to cleanse the skin and exhibit antibacterial activity. Staphylococcus aureus is the cause of skin infections. Liquid soap is a type of soap that can protect the skin against microorganisms, generally caused by S. aureus. This study aims to develop an antibacterial liquid soap containing kecombrang stem extract, in accordance with the quality requirements of liquid soap, and to determine its antibacterial activity against S. aureus. The extract is formulated into four liquid soap formulas, namely F0, F1, F2, and F3. Physical evaluations include organoleptic properties, homogeneity, pH, liquid soap foam height, viscosity, free alkali content, specific gravity, and antibacterial tests using the well diffusion method. In the organoleptic test, the liquid preparation is brown and has a distinctive odor, with a pH value of around 10.61 to 10.85. The foam height ranges from 33 to 93 mm, viscosity is 412 to 489 cP, specific gravity is 1.02 to 1.08, and free alkali content is 0.05 to 0.16%. Liquid soap with ethanol extract from kecombrang stem inhibits the growth of S. aureus bacteria, with inhibition zones of 9.2 mm for F1, 14.8 mm for F2, and 16 mm for F3, all with p-values <0.05. All formulas met the quality requirements for liquid soap, and F3 (17% extract) demonstrated the highest antibacterial activity.